2020
DOI: 10.1111/jgs.16844
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Optimize Medication Data Analysis in Clinical Cohort Studies

Abstract: OBJECTIVES Methods for pharmacoepidemiologic studies of large‐scale data repositories are established. Although clinical cohorts of older adults often contain critical information to advance our understanding of medication risk and benefit, the methods best suited to manage medication data in these samples are sometimes unclear and their degree of validation unknown. We sought to provide researchers, in the context of a clinical cohort study of delirium in older adults, with guidance on the methodological tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Finally, we used a directed acyclic graph, a method validated in pharmaco-epidemiology, to model and identify potential confounders that require conditioning when estimating causal effect in quasi-experimental studies [43, 44]. To our knowledge, no other study has used this method to explore a CP intervention, but Duprey et al [45] used a directed acyclic graph to model and analyse the potential interactions between different factors, such as age and urinary retention, and anticholinergic drug use and delirium.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Finally, we used a directed acyclic graph, a method validated in pharmaco-epidemiology, to model and identify potential confounders that require conditioning when estimating causal effect in quasi-experimental studies [43, 44]. To our knowledge, no other study has used this method to explore a CP intervention, but Duprey et al [45] used a directed acyclic graph to model and analyse the potential interactions between different factors, such as age and urinary retention, and anticholinergic drug use and delirium.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…2 Thus, in SAGES, the diagnosis of delirium was based mostly on CAM assessments and, for most patients, without corroborating clinical notes. 2,3 Duprey et al 1 state, “all medication exposure was confirmed to precede delirium development for individuals who were delirium positive before being entered into the [analytical] model.” Although confirming the temporal sequence increases the chance that a given medication caused delirium, 4 we posit that the authors’ results likely overestimated the causal effect of medications on delirium.…”
Section: To the Editormentioning
confidence: 60%
“…Later that day, when the second CAM assessment was made, the patient satisfied the CAM criteria for delirium. Thus, the 2:00 am administration of benzodiazepine preceded the second CAM assessment and, using the methods of Duprey et al, 1,4 a causative link between benzodiazepine and delirium would be inferred. However, that conclusion would have been incorrect.…”
Section: To the Editormentioning
confidence: 99%
“…Medications were coded by class using the American Hospital Formulary System (AHFS) classifications. 17 Additionally, total anticholinergic activity was quantified with each medication being assigned a value from 0 to 3, based on the strength of the agent's anticholinergic activity according to the Anticholinergic Cognitive Burden (ACB) scale and the Anticholinergic Drug Score (ADS). 17 If a class of medications had a prevalence <5% in either the prehospital or postsurgical period, then the medication class was excluded from this time period.…”
Section: Exposurementioning
confidence: 99%